2010
DOI: 10.1111/j.1749-6632.2010.05756.x
|View full text |Cite
|
Sign up to set email alerts
|

House calls revisited: leveraging technology to overcome obstacles to veteran psychiatric care and improve treatment outcomes

Abstract: Despite an increasing number of military service members in need of mental health treatment following deployment to Iraq and Afghanistan, numerous psychological and practical barriers limit access to care. Perceived stigma about admitting psychological difficulties as well as frequent long distances to treatment facilities reduce many veterans' willingness and ability to receive care. Telemedicine and virtual human technologies offer a unique potential to expand services to those in greatest need. Telemedicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…It should be noted that this favorable rating does not account for those withdrawing from the eGetgoing condition prior to experiencing the videoconferencing platform. Yet these findings are consistent with results from several studies showing that videoconferencing technology is well tolerated by patients receiving care in many areas of medicine and psychology, with outcomes comparable to usual care interventions (Koch, 2012; Olden at al., 2010; Steel et al, 2011). …”
Section: 0 Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It should be noted that this favorable rating does not account for those withdrawing from the eGetgoing condition prior to experiencing the videoconferencing platform. Yet these findings are consistent with results from several studies showing that videoconferencing technology is well tolerated by patients receiving care in many areas of medicine and psychology, with outcomes comparable to usual care interventions (Koch, 2012; Olden at al., 2010; Steel et al, 2011). …”
Section: 0 Discussionsupporting
confidence: 89%
“…A meta-analysis by Spek et al (2007) found that web-based interventions were better attended and more effective when accompanied by direct therapist involvement, findings that dovetail with other studies reporting strong associations between counseling attendance and improved substance abuse outcomes (King & Brooner, 2008; McLellan et al, 1993). Studies focusing on psychiatric and other clinical populations have reported at least comparable outcomes in web-based versus traditional in-person service delivery (Backhaus et al, 2012; Deen et al, 2012; Koch, 2012; Olden et al, 2010; Shore, 2013). …”
Section: 0 Introductionmentioning
confidence: 99%
“…Although the number of articles being published on VCP has increased in recent years, there remains a need for additional large-scale clinical trials to further assess the efficacy and effectiveness of VCP. of psychotherapies have been demonstrated to be effective in treating mental disorders, yet practical and psychological factors often prevent patients from receiving mental health care (Olden, Cukor, Rizzo, Rothbaum, & Difede, 2010). One such factor is the location in which mental health services are available.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Program/Project descriptions Antonacci et al, 2008Cartreine et al, 2010Bee et al, 2008Capner, 2000Hailey et al, 2008Freir et al, 1999Hilty et al, 2004Gammon et al, 1996Monnier et al, 2003Kuulasmaa et al, 2004Norman, 2006Mielonen et al, 2002Morland et al, 2009Olden et al, 2010Wright et al, 1998 115 VIDEOCONFERENCING PSYCHOTHERAPY…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Some veterans have reported heightened concerns about the security of the video transmissions, and some have been wary of other people, noises, or items in the therapist's room. Others have expressed a preference for the remote nature of VTC because they could "lower of psychotherapies have been demonstrated to be effective in treating mental disorders, yet practical and psychological factors often prevent patients from receiving mental health care (Olden, Cukor, Rizzo, Rothbaum, & Difede, 2010). One such factor is the location in which mental health services are available.…”
Section: Lessons Learnedmentioning
confidence: 99%